Exploring essential oil-based bio-composites: molecular docking and in vitro analysis for oral bacterial biofilm inhibition - Ullah, Niamat; Hasnain, Syed Zia Ul; Baloch, Rabia; Amin, Adnan; Nasibova, Aygun; Selakovic, Dragica; Rosic, Gvozden Luka; Islamov, Sokhib; Naraliyeva, Nasibakhon; Jaradat, Nidal; Mammadova, Afat O (Frontiers in Chemistry, 2024)
Oral Bacterial biofilms are main reason for progression of resistance to antimicrobial agents that may lead to severe conditions including periodontitis and gingivitis. Essential oils based nano-composites can be a promising treatment option here. We investigated cardamom, cinnamon and clove essential oils for their potential in treatment of oral bacterial infections using in vitro and computational tools. A detailed analysis of the drug-likeness and physicochemical properties of all constituents was performed. Molecular docking studies revealed that the binding free energy of carbopol-940 and eugenol complex was -2.0 kcal/mol, Carbapol 940-Anisaldehyde binding free energy was -1.9 kcal/mol while Carbapol940-Eugenol-Anisaldehyde complex had -3.4 kcal/mol. Molecular docking was performed against transcriptional regulator genes 2XCT, 1JIJ, 2Q0P, 4M81 and 3QPI. Eugenol cinnamaldehyde and cineol presented strong interaction with targets. The essential oils were analyzed against Staphylococos aureus and Staphylococos epidermidis isolated from oral cavity of diabetic patients. The cinnamon and clove essential combination presented significant MICs (0.0625/0.0312 mg/mL) against Staphylococos epidermidis and Staphylococos aureus (0.0156/0.0078 mg/mL). In the antiquorum sensing activity cinnamon and clove oil combination presented moderate inhibition (8 mm) against Chromobacterium voilaceum with substantial violacine inhibition (58±1.2%). Likewise, a significant biofilm inhibition was recorded in case of Staphylococos aureus (82.1±0.21%), and Staphylococos epidermidis (84.2±1.3%) in combination. It was thus concluded that combination of clove: cinnamon essential oil based formulation can be employed for preparation of stable nanocomposite and use of Carbapol-940 can be used as compatible biopolymer.